2013
DOI: 10.2220/biomedres.34.87
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell adhesion molecule (EpCAM) overexpression is correlated with malignant potentials of intraductal papillary mucinous neoplasms (IPMNs) of the pancreas

Abstract: Intraductal papillary mucinous neoplasms (IPMNs) of the pancreas exhibit a wide range of histopathological variation. Epithelial cell adhesion molecule (EpCAM) is a 40 kDa type I membrane protein that is known to be highly expressed in epithelial carcinomas. In this study, we examined immunohistochemical expression of EpCAM in the pancreatic IPMNs in order to clarify its clinicopathological significance. We analyzed 51 cases of surgically resected IPMNs: 32 cases of adenoma; 6 cases of non-invasive carcinoma; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…On the other hand, extracellular matrix signalling pathways (and hence, tumour stroma interaction) were found to be the most upregulated pathways. The finding is well supported by similar previous reports in PDAC [54] and also in IPMN, where other cell adhesion molecule overexpression has been linked to its malignant potential [55]. Moreover, inflammatory, especially TGF-beta signalling pathway has also been found to be overexpressed in high-risk IPMNs corroborating with the existing reports [56].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, extracellular matrix signalling pathways (and hence, tumour stroma interaction) were found to be the most upregulated pathways. The finding is well supported by similar previous reports in PDAC [54] and also in IPMN, where other cell adhesion molecule overexpression has been linked to its malignant potential [55]. Moreover, inflammatory, especially TGF-beta signalling pathway has also been found to be overexpressed in high-risk IPMNs corroborating with the existing reports [56].…”
Section: Discussionsupporting
confidence: 90%
“…This further supports the concept that mucinand mixed human CCA display different cells of origin and that an EpCAM+ cell could represent a candidate cell for mucin-CCA. Going back to the similarities between CCA, ductal pancreatic adenocarcinoma, and colorectal cancer, EpCAM overexpression has been correlated with malignant potential of IPMNs [60] and a novel genetic disorder of Lynch syndrome characterized by EpCAM gene deletion has been recently described [61]. These observations further support the hypothesis of a common cell of origin of these cancers (EpCAM+ cell) located in the glands of the original tissues ( Figure 2).…”
Section: Pbgs and Cholangiocarcinomasupporting
confidence: 59%
“…A target that is currently being explored in GC is the epithelial cell adhesion molecule (EpCAM or CD326). EpCAM is a 40-kDa type I transmembrane glycoprotein that is known to be highly expressed in epithelial carcinomas and serves as a prognostic factor[7]. Several studies pointed that EpCAM was identified as a one of tumour stem cell markers and an potential target for cancer therapy[8].…”
Section: Introductionmentioning
confidence: 99%